Effect of interventions on surgical site infections in Sub-Saharan Africa: a systematic review - Fekadeselassie Berhe; Tefera Belachew; Kalkidan Hassen (BMC Surgery)
Abstract Background Surgical site infections (SSI) are a major concern due to their contributions to morbidity, economic loss, and death among individuals who underwent operations in healthcare institutions. To decrease this infection, various pharmacological and non-pharmacological interventions have been devised and implemented for major surgery patients. Pharmacological interventions include the provision of antibiotic prophylaxis and antiseptic agents, whereas non-pharmacological interventions encompass programmatic interventions such as protocols, policies, quality improvement initiatives, training, and education that are given at the institutional level. However, the effect of particularly non-pharmacological interventions on the reduction has not been comprehensively evaluated for over a decade. This systematic review attempts to synthesize a piece of evidence on the effect of non-pharmacological intervention in Sub-Saharan Africa on minimizing SSI and enhancing health outcomes. Methods Databases including MEDLINE, Google Scholar, Cochrane Library, AJOL, Hinari, search platforms, and open-access repositories were accessed. Two investigators conducted a literature selection process, and the quality of selected articles was assessed using a JBI quality evaluation checklist. Results A total of 11 studies that met the inclusion criteria were analyzed. Three main intervention categories were identified, which focused on improving adherence to protocol, policy change or induction, and delivery of multimodal strategies. These interventions led to a reduction in SSI rates in varying degrees (15% to 95%). Multimodal interventions are the most widely implemented and comprehensive approaches that integrate multiple evidence-based practices, which have demonstrated a substantial reduction of SSI in different surgical populations. The rates of improvement with these interventions were influenced by intervention type, patient characteristics, surgical urgency, healthcare setting, follow-up time, and criteria for measuring the outcomes that may influence the SSI rates. Conclusion Interventions focusing on policy, protocol, and multimodal strategies can effectively reduce SSI rates, with the latter being the most effective. Patient and clinical characteristics, along with the healthcare setting, were influential factors affecting the interventions' impact on SSI. This systematic review is registered in PROSPERO, in the number CRD42024524963.